Evaluating the impact of COVID-19 on the profitability metrics of Saudi Arabian banks: A panel data analysis - Elmahgop, Faiza Omer (Asian Journal of Economic Modelling, 2024)
This study aims to evaluate the impact of the COVID-19 pandemic on the profitability of Saudi Arabian banks from Q1 2015 to Q2 2023. Using quantitative analysis of panel data from ten banks, the study assesses profitability through Return on Assets (ROA) and Return on Equity (ROE). Independent variables include bank-specific factors (Capital Ratios (CPTL), Operational Efficiency (OPEF), Deposits (DEP), Bank Size (SIZE)) and country-specific factors (Inflation (INF), Gross Domestic Product (GDP)), with the pandemic as a moderating factor. The findings reveal varied relationships between these variables and bank profitability. A significant negative relationship is observed between CPTL and ROE, suggesting that higher capital ratios may decrease profitability. OPEF and SIZE also show significantly negative relationships with both ROA and ROE, indicating that increased operational efficiency and bank size could lead to lower profitability. Conversely, DEP positively correlates with ROE, implying that banks with higher deposits achieve better equity returns. Interestingly, GDP and INF do not significantly affect bank profitability. These insights highlight the resilience and operational dynamics of the Saudi banking sector during COVID-19, emphasizing its robustness. The findings offer practical implications for policymakers, regulators, and banks in preparing for future systemic shocks and ensuring the sector’s sustainability and stability.